Rethinking Heavy Penalties and Misdemeanors for Drug Crimes in China—Discussing the Legislative History and Status of Drug Crimes - Chuyan Wu (Studies in Law and Justice, 2023)
Felonism in drug crimes has been a long-standing problem in Chinese legislation and judicial practice, with historical and even political factors involved. China’s drug legislation has undergone a process from the last century to the present, from scratch to maturity, but it should still be noted that felonism on drug crimes is still a serious and urgent problem today. As a non-violent crime, the current penalties for drug crimes do not match their social harms, and the heavy-handedness of drug crimes can hardly reduce the occurrence of drug crimes. To treat drug crimes, the future can start from restricting, or even abolishing, the death penalty, attaching importance to life imprisonment without commutation or parole, and focusing on the application of property penalties, and treating drug crimes as a comprehensive misdemeanor in order to conform to the principle of matching crime with punishment.